Terpenes and Terpenoids 2018
DOI: 10.5772/intechopen.77399
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of South African Lamiaceae: Structures and Biological Activity of Terpenoids

Abstract: South Africa flora is one of the most important mega floras with high endemic species percentage. Lamiaceae is an important family in South Africa with ±308 species in 41 genera and contains many important plants (~23%) traditionally used for treatment of different human diseases. The chemical profile of Lamiaceae is very rich in terpenoids in general and more specifically diterpenes. Genera like Leonotis and Plectranthus are well studied, while on the other hand, genus like Stachys (~41 species, ~50% endemic)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Most of the species are herbaceous or shrubby, and trees are scarce. The most well-known genus is Salvia (900), followed by Scutellaria (360), Stachys (300), Plectranthus (300), Hyptis (280), Teucrium (250), Vitex (250), Thymus (220), Nepeta (200), and Clerodendrum (150) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the species are herbaceous or shrubby, and trees are scarce. The most well-known genus is Salvia (900), followed by Scutellaria (360), Stachys (300), Plectranthus (300), Hyptis (280), Teucrium (250), Vitex (250), Thymus (220), Nepeta (200), and Clerodendrum (150) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Many of these diseases are caused by bacterial infections and numerous studies have reported antibacterial properties for species of this genus. [41][42][43] However, many of these studies either do not quantify the activity, or report low to moderate activity for the extracts and oils of these plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of chromatographic data and reference compounds limits their use in such useful applications [ 314 ]. In a review by Hussein (2018) [ 210 ], a thorough account of the diterpenoids isolated from southern African species, especially from the genera Coleus , Leonotis , Plectranthus , Salvia , and Tetradenia, is presented.…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Paton. Compounds such as coleon U and V, royleanone and horminone were identified from C. grandidentatus with coleon U exhibiting potent cytotoxicity against human cancer cell lines and has been deemed a promising anticancer compound needing further investigation [ 210 ]. Coleus comosus has been well studied with twenty compounds identified, eleven of which are neoclerodanes, seven labdanes and several abietanes [ 210 ].…”
Section: Chemical Compoundsmentioning
confidence: 99%
See 1 more Smart Citation